Melanoidin, a Food Protein-Derived Advanced Maillard Reaction Product, Suppresses Helicobacter pylori in vitro and in vivo - Hiramoto, Shigeru; Itoh, Kazuro; Shizuuchi, Satomi; Kawachi, Yasuji; Morishita, Yoshirou; Nagase, Masao; Suzuki, Yoshio; Nobuta, Yukio; Sudou, Yuhshi; Nakamura, Osamu; Kagaya, Imae; Goshima, Hideo; et al. (Helicobacter (Cambridge, Mass.), 2004)
ABSTRACT Background.  Extracellular urease proteins located on the surface of Helicobacter pylori are gastric mucin‐targeted adhesins, which play an important role in infection and colonization to the host. In this study we have determined the inhibitory activity of a variety of melanoidins, protein‐derived advanced Maillard reaction products, ubiquitously found in heat‐treated foods, on urease‐gastric mucin adhesion. In addition, we have determined the anticolonization effect of melanoidin I, prepared by the Maillard reaction between casein and lactose, in an animal model and in human subjects infected with this bacterium. Methods.  The inhibitory activity of each compound was determined by a competitive binding assay of labeled gastric mucin to plate‐immobilized urease. Melanoidin I was used in an in vivo trial using euthymic hairless mice as an infection model. Melanoidin I was consumed for 8 weeks by subjects infected with H. pylori. The [13C] urease breath test and H. pylori‐specific antigen in the stool (HpSA) test were performed on subjects at week 0 and week 8. Results.  A variety of food protein‐derived melanoidins strongly inhibited urease‐gastric mucin adhesion in the concentration range of 10 µg/ml to 100 µg/ml. In particular, melanoidin I significantly (p < .05) suppressed colonization of H. pylori in mice when given for 10 weeks via the diets. Eight weeks daily intake of 3 g melanoidin I significantly (p < .05) decreased the optical density of HpSA in subjects. Conclusion.  Foods containing protein‐derived melanoidins may be an alternative to antibiotic‐based therapy to prevent H. pylori that combines safety, ease of administration and efficacy.